Uporaba podporne tehnologije pri bolnikih z mielomeningokelo na oddelku za (re)habilitacijo otrok na Univerzitetnem rehabilitacijskem inštitutu Republike Slovenije - Soča - Žigon, Suzana Albina (Rehabilitacija (Ljubljana), 2012)
Background: Myelomeningocele is the most serious form of spina bifida, the congenital malformation of the neural-tube. The defect occurs when a sac containing part of the spinal cord and its meninges protrude through a gap in the vertebral column; it is frequently accompanied by hydrocephalus. The aim of the study was to analyze assistive technology use among patients with myelomeningocele and their education. We also wanted to find out if there is a difference between patients with myelomeningocele without hydrocephalus and those with hydrocephalus who were operated regarding educational program. Methods: The study was retrospective. We included patients with myelomeningocele with and without hydrocephalus who were treated between 1 January, 2005, and 30 June, 2011, at the Department for Children (Re)Habilitation of the University Rehabilitation Institute in Ljubljana. The analysis addressed age, gender, age at shunt placement, current education program, completed education, use of wheelchair, braces and walking aids, and inclusion in bowel and bladder program. Results: The study included 47 patients between 4 months and 22 years of age. There were 19 patients of male and 28 of female gender. More than half of them have a shunt in place. All the patients were operated before the age of 6 months. Twenty-two percent attended special education programs and 25 % were included in regular education; 12 % attended kindergarten, 12 % were not included in education programs; 44 % of patients completed less then high school, 44 % completed high or vocational school, and 11 % completed facilitated regular education. Sixty-four percent of the patients used orthoses, 27 % used walking aids. All the patients use some kind of assistive technology but there are differences in the type of assistive technology between age groups. In older age groups, there was more use of wheelchair and less use of orthoses. Almost all patients use medical programs for neurogenic bladder and most patients use programs for neurogenic bowel. We could not perform an analysis of differences in current or completed educational program with respect to the age at which the patients with hydrocephalus were operated, because all the patients who needed such operation were operated before the age of 6 months. Conclusions: We believe that good treatment and rehabilitation programs for patients with myelomeningocele are in place in our country. If the patients have hydrocephalus, they have the operation before the age of 6 months. All patients use medical programs for neurogenic bladder and bowel, and participate in educational programs according to their abilities. Further studies should address satisfaction of the patients and their caregivers with the provision of rehabilitation programs and assistive technology.
Keywords: Education; Gait; hidrocefalus; hoja; Hydrocephalus; izobraževanje; Meningomyelocele; mielomeningokela; podporna tehnologija; samopomagala; samopripomočki; Self-Help Devices; šolanje